A Case Study On Maxis Communications - Soong, Jen Nee (2008)
The objective of this paper s to study the Malaysian telecommunication industry, specifically focusing on Maxis. The ultimate goal of this project is to evaluate the company's current position, identify its current issues and develop appropriate strategies to improve the company, gearing towards its vision.